1995
DOI: 10.1515/cclm.1995.33.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Faecal Fat by Near-Infrared Spectroscopy

Abstract: The applicability of near-infrared spectroscopy to determine the amount of fat in faeces has been investigated. Near-infrared spectroscopy was favourably compared with the well known titrimetric method ( Van de Kamer et al., J Biol Chem 1948; 177:347-55). A good correlation between near-infrared spectroscopy and the titrimetric method was found. The measurement of faecal fat by near-infrared spectroscopy is found to be more precise than the manual method. Moreover, near-infrared spectroscopy is shown to be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Therefore, the applicability of this equipment is hampered by the necessity of substantial numbers of samples to be analysed in order to justify the purchase of the apparatus. 5 Franck et al 8 described the use of a FT-IR method, employing an ATR sampling device, for the prediction of faecal fat. They made preliminary sample selections, based on the faecal water content and the sample homogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the applicability of this equipment is hampered by the necessity of substantial numbers of samples to be analysed in order to justify the purchase of the apparatus. 5 Franck et al 8 described the use of a FT-IR method, employing an ATR sampling device, for the prediction of faecal fat. They made preliminary sample selections, based on the faecal water content and the sample homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…These are biological samples from which the sample compositions have been determined by means of a generally accepted method, such as that of Van de Kamer. However, Bekers et al 5 highlighted the need to create a new calibration curve in every clinical chemical laboratory when using secondary reference samples. A paper describing a multicentre trial showed that the results of the Van de Kamer method were poorly exchangeable.…”
Section: Introductionmentioning
confidence: 99%
“…They were reported to have 100% sensitivity and 96% specificity, but radioisotopes or nonradioactive isotopes and facilities for their determination are not available in most laboratories and the results are very expensive. Recently, near infrared spectrometry and NRM spectrometry were shown to be very sensitive and specific methods to determine the amount of fat in feces [111]. The steatocrit is a very interesting, simple, inexpensive, rapid, semiquantitative micromethod that uses an aliquot of homogeinized stool and centrifugation of the sample to determine the percentage of fat in the specimen [109].…”
Section: Tests For Detecting Functional Abnormalities Fat Malabsorptimentioning
confidence: 99%